Effect of Dietary Pattern and Statin Therapy on Gene Expressions in Gastrointestinal Tract and Relation to Atherosclerosis in the Ossabaw Pig - YE, SHUMAO. (Tufts University. Tisch Library., 2020)
Thesis (Ph.D.)--Tufts University, 2020.; Submitted to the Dept. of Biochemical and Molecular Nutrition.; Advisor: Alice Lichtenstein.; Committee: Nirupa Matthan, Stefania Lamon-Fava, Jerrold Turner, and Xiang-Dong Wang.; Keywords: Nutrition, Biochemistry, and Molecular biology.